Indole and synthetic derivative activate chaperone expression to reduce polyQ aggregation in SCA17 neuronal cell and slice culture models - Kung, Pin-Jui (Dove Medical Press, 2014)
In spinocerebellar ataxia type 17 (SCA17), the expansion of a translated CAG repeat in the TATA box binding protein (TBP) gene results in a long polyglutamine (polyQ) tract in the TBP protein, leading to intracellular accumulation of aggregated TBP and cell death. The molecular chaperones act in preventing protein aggregation to ameliorate downstream harmful events. In this study, we used Tet-On SH-SY5Y cells with inducible SCA17 TBP/Q(79)-green fluorescent protein (GFP) expression to test indole and synthetic derivative NC001-8 for neuroprotection. We found that indole and NC001-8 up-regulated chaperone expression to reduce polyQ aggregation in neuronal differentiated TBP/Q(79) cells. The effects on promoting neurite outgrowth and on reduction of aggregation on Purkinje cells were also confirmed with cerebellar primary and slice cultures of SCA17 transgenic mice. Our results demonstrate how indole and derivative NC001-8 reduce polyQ aggregation to support their therapeutic potentials in SCA17 treatment.